A Bibliometric Analysis of Employee Retention in Digital Era: Trends, Key Contributors, and Future Direction - Sastra, De Fitrah Sukmana; Hanifah, Siti (Banking & Management Review, 2025)
Introduction/Main Objectives: In today’s digital era, employee retention has become a critical challenge for organizations. High turnover rates negatively affect both productivity and profitability. This study examines the role of digital technology in strengthening human resource management strategies to retain talent in a highly competitive environment. Background Problems: This research investigates the economic and organizational implications of employee retention, with a particular focus on how digital technology influences HR practices. It addresses the central research question: “How does digital technology contribute to innovative human resource strategies that enhance employee retention?”. Novelty: This study contributes to the existing literature by filling a gap concerning the role of digital technology in employee retention. It employs a bibliometric approach to analyze three decades of research trends, offering new insights into adaptive work environments. Research Methods: The study applies bibliometric analysis to 269 articles indexed in Scopus between 1989 and 2024. The data were processed and visualized using VOSviewer software to identify major themes, emerging trends, and influential factors in employee retention research. Finding/Results: The analysis highlights several critical factors influencing employee retention, such as dynamics in emerging economies, the rise of hybrid work models, and the importance of leadership, work-life balance, and flexibility in the post-pandemic era. Conclusion: The study concludes that digital technologies play a vital role in improving HR strategies and enhancing employee retention. It emphasizes the need to further explore retention issues in developing countries and to invest in technology and training programs. Such investments can strengthen employee engagement and ensure long-term organizational success.